2023
DOI: 10.3389/fnut.2023.1213255
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic nutritional index as a reliable prognostic indicator for advanced lung cancer patients receiving immune checkpoint inhibitors

Abstract: BackgroundPrognostic nutritional index (PNI) has been identified as a reliable prognostic factor for cancer adjuvant therapy. However, its prognostic value in lung cancer patients receiving immune checkpoint inhibitors (ICIs) remains inconclusive.MethodA systematic literature review and meta-analysis was performed based on online databases before March 1th 2023. The correlation of PNI with overall survival (OS) or progression-free survival (PFS) was determined using the hazard ratios (HRs) coupled with 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…A recent report suggested the nutritional status may be correlated with the proportion and function of immune cells (such as T and memory cells) in the tumor microenvironment, therefore affecting the clinical e cacy of the immunotherapies [26] . Yan's study reported that PNI is a reliable prognostic factor for advanced lung cancer patients receiving immune checkpoint inhibitors-based therapies [27] . Yamada's study showed that low pretreatment PNI was an effective independent prognostic factor for shorter OS of patients with metastatic hormone-sensitive prostate cancer [28] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggested the nutritional status may be correlated with the proportion and function of immune cells (such as T and memory cells) in the tumor microenvironment, therefore affecting the clinical e cacy of the immunotherapies [26] . Yan's study reported that PNI is a reliable prognostic factor for advanced lung cancer patients receiving immune checkpoint inhibitors-based therapies [27] . Yamada's study showed that low pretreatment PNI was an effective independent prognostic factor for shorter OS of patients with metastatic hormone-sensitive prostate cancer [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The systemic immune-inflammation index (SII), combining platelet count and NLR, is an unfavorable factor affecting the PFS of NSCLC patients receiving PD-1 inhibitors ( 13 ). Our team has previously proved prognostic nutritional index (PNI) as a reliable prognostic indicator for both ICI-treated NSCLC and small cell lung cancer (SCLC) patients ( 14 ). However, these prognostic indexes are mainly based on laboratory tests, ignoring individual status such as performance status (PS) and smoking status, which may be also crucial for ICI efficacy ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%